Application of Vehicle Mounted Accelerometers to Measure Pavement Roughness - Yuchuan Du; Chenglong Liu; Difei Wu; Siyu Li (International Journal of Distributed Sensor Networks)
To enhance the efficiency of pavement roughness measurement and reduce the cost, an integrated and wireless transfer based measuring system was developed. The proposed system can obtain vehicles status and location data via wireless acceleration sensors and GPS, calculate the international roughness index (IRI) by power spectral density analysis, and provide reports automatically. This paper presents the architecture of the proposed system, consisting of data collector, car mounted terminal, and information platform. Two wireless communication systems (ZigBee and 3G modules) were utilized to transfer the data and construct network between the components. The information platform implemented an acceleration-IRI model to calculate IRI, and a GPS based distance algorithm was employed to segment the measured road per 1 km. The various results are saved in an Oracle database, displayed on the digital map and made available to the mobile terminal. Several field tests of the prototype system were conducted in Huzhou, Zhejiang province in China. The results show that, compared to the laser roughness testing method, the relative error of this proposed system is less than 10%, which verifies the accuracy, effectiveness, and reliability of the proposed measuring system.